Necessary and sufficient conditions for the oscillation of delay differential equation with a piecewise constant argument - H. A. Agwo (International Journal of Mathematics and Mathematical Sciences)
The characteristic equation for an equation with continuous and piecewise constant argument in the form x˙(t)+px(t−τ)+qx([t−k])=0    where  p, q∈ℜ, τ∈ℜ+and  k∈ℵ is presented, which when q=0 reduces to f(λ)=λ+e−λτ=0